2007
DOI: 10.1590/s0073-47212007000300011
|View full text |Cite
|
Sign up to set email alerts
|

Dípteros minadores e seus parasitóides em plantas de crescimento espontâneo em pomar orgânico de citros em Montenegro, RS, Brasil

Abstract: ABSTRACT. Diptera leafminers and their parasitoids in spontaneous vegetation in organic citrus orchard in Montenegro, RS, Brazil. Leafminers and their parasitoids communities analysis is necessary to supply information about the biotic regulation and to maintenance of the biodiversity in the agroecosystem. This study aimed to register Diptera leafminers and their parasitoids, present in the vegetation spontaneously growing at the citrus orchard from May 2003 to May 2004. The work was conducted in Montenegro, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
(2 reference statements)
0
1
0
1
Order By: Relevance
“…Um dos principais inimigos naturais dessa espécie de praga é o parasitóide Opius sp. (Hymenoptera: Braconidae), que controla as larvas, que são os que causam os danos (Santos et al, 2008). Estes parasitóides utilizam as larvas como hospedeiras das suas progênies, ao ovipositar no interior destas, para que a larva do parasitóide possa alimentar-se do conteúdo interno da lagarta, emergindo, posteriormente, um ou mais adultos.…”
Section: Discussionunclassified
“…Um dos principais inimigos naturais dessa espécie de praga é o parasitóide Opius sp. (Hymenoptera: Braconidae), que controla as larvas, que são os que causam os danos (Santos et al, 2008). Estes parasitóides utilizam as larvas como hospedeiras das suas progênies, ao ovipositar no interior destas, para que a larva do parasitóide possa alimentar-se do conteúdo interno da lagarta, emergindo, posteriormente, um ou mais adultos.…”
Section: Discussionunclassified
“…However, Santos et al . () reported that this species (reported as Phyllocnistis sp.) occurs year around in the area, with higher densities found during the winter and spring.…”
Section: Taxonomymentioning
confidence: 98%